Labor-force participation rates and the informal value of unemployment rates: Evidence from disaggregated US data - Magnus Gustavsson; Pär Österholm (Uppsala University, Department of Economics, 2010)
The informational value of the aggregate US unemployment rate has recently been questioned because of a unit root in the labor-force participation rate; the lack of mean reversion implies that long-run changes in unemployment rates are highly unlikely to reflect long-run changes in joblessness. This paper shows that this critique also extends to unemployment rates for sub-populations, such as prime-aged males.
urn:nbn:se:uu:diva-130061
Keywords: C22; E24; J21; 330; Mean reversion; Unit-root test; Erwerbstätigkeit; Arbeitslosigkeit; Mean Reversion; Unit Root Test; USA